Die Aufhebung des Schwärmers - Specht, Benjamin (KulturPoetik, 2019)
The widespread anthropological concept of the Schwärmer links many psychological, philosophical, religious and aesthetical ideas of late Enlightenment. As Likemany notions of that period, it is preserved but transformed according to the principles of transcendental philosophy and poetics in Early Romanticism. The article retraces these shifts particularly in the theoretical and literary work of Friedrich von Hardenberg (Novalis). His pre-Romanticist literary remains, which have been neglected by literary studies, contain many references to the contemporary Schwärmer debate. When Hardenberg eventually becomes Novalis in the 1790's, he relies on these references as a premise to his concept of magical idealism and his literary technique of romantisieren. From this perspective, the idea of the romantic poet in his novel Heinrich von Ofterdingen turns out to be a refined version of the Schwärmer.
CRIS-Team Scopus Importer:2019-11-26